PKM Peningkatan Kemampuan Berbicara pada Karang Taruna RT 007 RW 05 Kelurahan Tanjung Barat, Jagakarsa Jakarta Selatan - Doni Anggoro Ari Santoso; Agung Prasetyo (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
This activity is carried out for youth groups of RT 007 RW 005 Tanjung Barat Jagakarsa, South Jakarta. The purpose of this community service activity is to increase the knowledge of youth in improving speaking skills. Good communications are needed by the youth in carrying organizational activities so the message can be easily understood by the audience. In communicating, it is also necessary to choose the right words so that sentences can be well structured and can be conveyed properly and easily understood. The writers felt that there are still many shortcomings in the youth organization of RT 007 RW 05, and it is necessary to add insight on how to improve speaking skills with other people.